Contradiction in motion : Hegel's organic concept of life and value - Hahn, Songsuk Susan (Cornell University Press, 2007)
""Everything is contradictory," Hegel declares in Science of Logic. In this analysis of one of the most difficult and neglected topics in Hegelian studies, Songsuk Susan Hahn tackles the status of contradiction in Hegel's thought. Properly philosophical thinking in the Hegelian mode recognizes that contradiction pervades all organic forms of life. Contradiction in Motion presents Hegel's doctrine of contradiction, once widely dismissed, as one deserving serious consideration. The book argues that contradiction is not a sign of error or incoherence, but rather plays an important role in the development of Hegel's system."--Jacket